2020
DOI: 10.3390/cancers12020376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Immune Checkpoints on Circulating Tumor Cells in Breast Cancer

Abstract: The role of CD47 and PD-L1 expression on circulating tumor cells (CTCs) remains unclear, and it is currently unknown whether their distribution varies between the blood and tumor tissue in breast cancer (BC). In this study, CD47 and PD-L1 expression was investigated a) on peripheral blood mononuclear cell (PBMC) cytospins from early (n = 100) and metastatic (n = 98) BC patients, by triple immunofluorescence for CD47/PD-L1/Cytokeratins, and b) on matched primary and/or metastatic tumor tissue from CTC-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 55 publications
7
73
2
Order By: Relevance
“…This is potentially related to the fact that spiking experiments may overestimate the performance of methods since cancer cell lines tend to be more homogenous compared to CTCs, which present significant individual heterogeneity and distinct profiles compared to cancer cell lines [ 53 ]. This hypothesis is in line with a recent finding showing a reduction in the cell mass and size of tumor cells undergoing epithelial-to-mesenchymal transition (EMT) [ 54 ], a process commonly identified on CTCs [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This is potentially related to the fact that spiking experiments may overestimate the performance of methods since cancer cell lines tend to be more homogenous compared to CTCs, which present significant individual heterogeneity and distinct profiles compared to cancer cell lines [ 53 ]. This hypothesis is in line with a recent finding showing a reduction in the cell mass and size of tumor cells undergoing epithelial-to-mesenchymal transition (EMT) [ 54 ], a process commonly identified on CTCs [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings, albeit preliminary, suggest that CTC characterization according to IDO and PD-L1 may promote our understanding of the mechanisms underlying immunotherapy resistance and may provide valuable prognostic information for NSCLC patients treated with anti-PD1 ICIs. Similarly, we recently demonstrated that the parallel assessment of innate (CD47) and adaptive (PD-L1) immune checkpoints on CTCs has significant prognostic and predictive implications in breast cancer [ 39 ]. Overall, the above observations highlight the importance of the phenotypic characterization of single CTCs in the effort to obtain a broader view of the systemic antitumor immune response and suggest that CTC analysis in real time might improve the stratification of patients treated with different immunotherapy strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations